Application of The Hungarian Rhapsody No. 2 song by Franz Liszt in the Tom and Jerry film from the episode The Cat Concerto - Alvriza Mohammed Fadly; Harry Tjahjodiningrat (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Cartoon films can not be separated from a song that is used as the Original Soundtrack, even the song became famous through the nature of the film media. The selection of songs is always adjusted to the genre of the film, in the Tom and Jerry cartoon series episode Cat Concerto there is a uniqueness, namely using songs as an accompaniment to the story narrative. How important is the presence of music in the art of motion pictures, and the choice of music is a very specific thing related to emotional considerations for a composer. Not all music can bring the side of expression to life in a film, because the role of music is related to the emotions of the audience. This study uses a qualitative method by describing the results of the analysis through reading music and pieces of pictures accompanied by music. The research focuses on the composition of The Hungarian Rhapsody No.2 as Narrator for the Cat Concerto Episode from the Tom And Jerry Cartoon. The results of this study can identify, categorize the creation of character movements with the composition The Hungarian Rhapsody No. 2 which is used as a film accompaniment. Found precision in placing the music on each scene.